Nanocomposite foams with balanced mechanical properties and energy return from EVA and CNT for the midsole of sports footwear application - Chang, Boon Peng (2023)
Polymer foam that provides good support with high energy return (low energy loss) is desirable for sport footwear to improve running performance. Ethylene-vinyl acetate copolymer (EVA) foam is commonly used in the midsole of running shoes. However, EVA foam exhibits low mechanical properties. Conventional mineral fillers are usually employed to improve EVA's mechanical performance, but the energy return is sacrificed. Here, we produced nanocomposite foams from EVA and multi-walled carbon nanotubes (CNT) using a chemical foaming process. Two kinds of CNT derived from the upcycling of commodity plastics were prepared through a catalytic chemical vapor deposition process and used as reinforcing and nucleating agents. Our results show that EVA foam incorporated with oxygenated CNT (O-CNT) demonstrated a more pronounced improvement of physical, mechanical, and dynamic impact response properties than acid-purified CNT (A-CNT). When CNT with weight percentage as low as 0.5 wt% was added to the nanocomposites, the physical properties, abrasion resistance, compressive strength, dynamic stiffness, and rebound performance of the EVA foams were improved significantly. Unlike the conventional EVA formulation filled with talc mineral fillers, the incorporation of CNT does not compromise the energy return of the EVA foam. From the long-cycle dynamic fatigue test, the CNT/EVA foam displays greater properties retention as compared to the talc/EVA foam. This work demonstrates a good balanced of mechanical-energy return properties of EVA nanocomposite foam with very low CNT content, which presents promising opportunities for lightweight-high rebound midsoles for running shoes.